A Social Survey on Asylum Seekers in and around Vienna in Fall 2015: Methodological Approach and Field Observations - Judith Kohlenberger; Isabella Buber; Bernhard Rengs; Zakarya Al Zalak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2016)
In late 2015, a survey called DiPAS (Displaced persons in Austria survey) was carried out in and around Vienna to study the socio-demographic characteristics, values and attitudes of asylum seekers arriving in Austria in 2015. In that year, the number of persons seeking refuge in Europe was substantially high, with Austria being the fourth largest receiving country of asylum seekers in Europe. This data collection is the first of its kind in Austria and to our knowledge the first in Europe focusing on the recent arrivals of Syrian, Iraqi, and Afghan asylum seekers. First results on human capital and attitudes of DiPAS respondents have been published recently. The current paper presents the methodological approach of collecting these data, experiences from survey preparation, and insights from the field phase. Findings address four key challenges faced by surveys of the highly mobile and vulnerable group of asylum seekers, namely (1) representativity, (2) language barriers, (3) ethical considerations, and (4) cultural diversity. We discuss concrete solutions and recommendations for similar (inter)national, cross-cultural surveys, and provide insights for planning longitudinal studies on displaced persons who recently arrived in Europe.
Keywords: 300; refugees; asylum seekers; irregular migration; survey; Syria; Iraq; Afghanistan; methodology; field phase